1990
DOI: 10.1002/jcla.1860040305
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric analysis of peripheral blood in the normal pediatric population by flow cytometry

Abstract: Lymphocyte subset analysis was performed on 114 healthy children and 84 healthy adults. Samples were prepared by a whole blood lysis technique and analyzed by flow cytometry. The percentage and total number of CD3+, CD4+, CD8+, and CD19+ lymphocytes were calculated for each of six age groups. A direct correlation with age was seen in the percentages of CD3+, CD4+, and CD8+ lymphocytes. The absolute number and percentage of total lymphocytes, the percentage and absolute number of CD19+ lymphocytes, and the abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 9 publications
4
21
0
Order By: Relevance
“…Then, T cell numbers continuously increase until age 30 years. After age 30 years, T cell numbers remain at a relatively stable level with a slow decline over time, as suggested by data (26,27). Our simulation results of T cell dynamics are within the normal range calculated from human data on cell numbers per mm 3 of blood, blood volume, and body weight (error bars in Fig.…”
Section: Predicting Total T Cell Numbers Total Sjtrec Levels and Sjsupporting
confidence: 85%
See 1 more Smart Citation
“…Then, T cell numbers continuously increase until age 30 years. After age 30 years, T cell numbers remain at a relatively stable level with a slow decline over time, as suggested by data (26,27). Our simulation results of T cell dynamics are within the normal range calculated from human data on cell numbers per mm 3 of blood, blood volume, and body weight (error bars in Fig.…”
Section: Predicting Total T Cell Numbers Total Sjtrec Levels and Sjsupporting
confidence: 85%
“…5 T cells, we divide sjTREC/PBMCs with the ratios: total lymphocytes/PBMCs and T cells/total lymphocytes over time (26,33,34), and then multiply by 1.5 ϫ 10 5 T cells. sjTREC data from Douek et al and Zhang et al were both measured using blood samples.…”
Section: Shown Inmentioning
confidence: 99%
“…This finding was not confirmed in our study, however. In addition, published work from different laboratories showed that both CD4 ϩ and CD8 ϩ cell counts increase with age with an unchanged CD4/CD8 ratio (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to T-cells, however, although some studies have reported changes in T cell levels, especially a decrease in the CD8 cells with increasing age [2,10,11,[32][33][34], other (older) have reported increase in CD4+ and /or CD8+ [24,35,36]. The impact of age on lymphocyte subsets is not well established, with contradictory results from various studies.…”
Section: A U T H O R P R O O F Future Science Groupmentioning
confidence: 99%